Locked Away: Percutaneous Closure of a Malignant Left Atrial Appendage to Constrain an Unresolvable Thrombus. (August 2016) - Dugo, Daniela; Bordignon, Stefano; Konstantinou, Athanasios; Perrotta, Laura; Fürnkranz, Alexander; Chun, Julian K.R.; Schmidt, Boris
Abstract : Supplemental Digital Content is available in the text.